Cabozantinib in Patients with Advanced Merkel Cell Carcinoma. (14th February 2018) - Rabinowits, Guilherme; Lezcano, Cecilia; Catalano, Paul J.; McHugh, Patricia; Becker, Hailey; Reilly, Megan M.; Huang, Julian; Tyagi, Ayushi; Thakuria, Manisha; Bresler, Scott C.; Sholl, Lynette M.; Shapiro, Geoffrey I.; et al.
Abstract : Background: This study sought to determine the efficacy and safety profile of cabozantinib in patients with advanced Merkel cell carcinoma (MCC). Experimental Design: This prospective, phase II, single‐institution trial enrolled patients with platinum‐failure, recurrent/metastatic MCC to receive cabozantinib 60 mg orally daily until disease progression, withdrawal from study, or severe toxicity. The primary endpoint was disease control rate. Secondary endpoints included overall survival (OS), progression‐free survival (PFS), and toxicity. Immunohistochemistry for VEGFR‐2, MET, and HGF expression and next‐generation sequencing of tumor tissue were performed and correlated with outcome. Results: Eight patients were accrued from January 24, 2014, to June 8, 2016. The study was closed prematurely because of toxicity and lack of responses. The most frequent adverse events were grades 1 and 2 and included anorexia, fatigue, nausea, hypothyroidism, and dysgeusia. Two patients developed nonhealing, painful ulcers and tumor‐skin fistula. One patient had stable disease for 8 months. One patient withdrew from the study after 2 weeks of therapy because of adverse events. Three patients required dose reduction because of toxicity. Median PFS and OS were 2.1 and 11.2 months, respectively. No expression of MET, HGF, or VEGFR‐2 was identified in tumor cells by immunohistochemistry of patients' tissue samples. Conclusion: Cabozantinib was poorly tolerated and did not demonstrate activity in patients with recurrent/metastatic, platinum‐failure MCC. It is unclear whether preselection of patients with the specific upregulation or genetic alteration in the targets for cabozantinib would have changed the results of this study. (Clinical trial identification number: NCT02036476) Implications for Practice: This phase II study demonstrated poor tolerability and lack of activity of cabozantinib in an unselected group of patients with advanced Merkel cell carcinoma. Although it is unclear whether preselection of patients with the specific upregulation and genetic alterations in targets for cabozantinib would have changed the results of this study, this would have likely led to an extremely rare patient population that would take many years to accrue. Abstract : Merkel cell carcinoma is a rare and aggressive neuroendocrine skin cancer, with a rising incidence. This article evaluates the feasibility of using cabozantinib in patients with advanced Merkel cell carcinoma whose disease failed platinum‐based therapy.